Teachers' Perception Towards The Use Of Google Document in Teaching and Learning Process - Noviska, Della Wilza; Aisyah, Siti; Yuniarti, Yuniarti; Ihsan, Muhammaad Taufik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
Google Docs is a free web-based application for creating, editing, and collaborating. This systematic review showed that using some Google documents resulted in developing English language learning and teaching. The writing was the biggest language skill investigated. Google Docs is a version of Microsoft Word that offers collaborative features that can be used to facilitate the teaching and learning process in the language classroom. The method used in writing this paper was a literature review based on collecting data and information that related to teachers' perceptions towards the use of Google Docs in the teaching and learning process. This paper has indicated the teachers’ perception toward the use of Google documents in the teaching and learning process in the classroom. In fact, Google Docs, while nearly all of them perceive that this learning tool is easy to use in the teaching and learning process and very helpful for teachers in the teaching and learning process.